PENGARUH PENDAPATAN, LAMA KERJA DAN STATUS FAMILI TERHADAP REMITAN TENAGA KERJA WANITA PROPINSI NUSA TENGGARA BARAT - Hj. Titiek Herwanti (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
This research took place in West Praya subdistrict (Mangkung Village), Jonggat subdistrict (Puyung Village). All places was in Central Lombok Region, West Nusa Tenggara Province. The objective of this research is to know the factors that  influence the number of remittance including it’s contribution toward household income, the changes of attitude according to environmetal perception and working ethos and also to know the influence of workers mobility toward the sustainable development in their region. This research have 90 respondents. 30 respondents represent return migrants, 30 respondents represent potensial migrants and 30 respondents respresent household migrant. The data of income, working period, and family’s status is taken from labor department. The result of this research shows that the income factors of destination country, working period and family’s status, influence the numbers of remittance. The income of household migrant and return migrants (which are 75,73% and 76,74%) increased because of the workers mobility. This situation also can bring positvef influence toward the environmental perception and working ethos, as well as giving contribute to sustainable development in their region.